Safety Barrier Functions for Human-Robot Interaction with Industrial Manipulators - Landi, Chiara Talignani; Ferraguti, Federica; Costi, Silvia; Bonfe, Marcello; Secchi, Cristian (2019 18th European Control Conference (ECC), 2019)
A change in the paradigm of Human-Robot Interaction has allowed to place robots nearby human operators, creating shared working environments. Industrial manipulators are becoming human helpers in different industrial tasks. As a consequence, human safety plays a leading role in the development of control algorithms. In this paper we propose an optimization-based algorithm that allows to avoid obstacles while minimizing the difference between the nominal acceleration input and the commanded one. Safety barriers are built around the robot links and allow to generate collision-free movements of the whole robot body. The algorithm is implemented on an Universal Robots UR5 in order to validate the proposed approach.